Le méthaniseur et le paysage - Fabrice Raffin; Camille Dormoy (Projets de Paysage)
This article proposes to analyse the landscape as a process relating to a collective action mobilising various human, quasi-human, and non-human groups (Akrich et al., 2006), with crossed, conflicting, and converging interests evolving over time, but who are also in situations of competition, indifference, accommodation, and even assimilation (Grafmeyer and Joseph, 2009). A definition of the landscape that therefore involves at the same time the actor-network theories and the sociological interactionist approach (Le Breton, 2012). Using ethnographic participative observation based on our role in the collective action, the aim is to analyse the process of the implementation of a development project contributing to the production of a landscape : the installation of a biogas plant 60 km from Paris. The article focuses on the omnipresence of environmental factors in the organisation of public debate and more precisely on the role of anthropized biodiversity as a framework. The notion of biodiversity is constructed through a systematically anthropomorphic or human-referenced perspective, through the mobilisation of science for the purposes of argumentation. It then intervenes in the constitution of audiences (Céfaï, 2015) and of problematic situations relating to land use planning, which are implicitly part of a struggle to maintain a landscape in its existing state.